Adolescents with obesity treated with exenatide maintain endogenous GLP-1, reduce DPP-4, and improve glycemic control - Stenlid, Rasmus; Cerenius, Sara Y.; Wen, Quan; Aydin, Banu Küçükemre; Manell, Hannes; Chowdhury, Azazul; Kristinsson, Hjalti; Ciba, Iris; Gjessing, Erik S.; Mörwald, Katharina; Gomahr, Julian; Heu, Verena; et al. (Frontiers in Endocrinology, 2023)
Background: GLP-1 receptor agonists (GLP-1RA) are increasingly used to treat adolescent obesity. However, the effect on endogenous GLP-1 secretory patterns following treatment in adolescents is unknown. The GLP-1RA exenatide was shown to significantly lower BMI and 2-hour glucose in adolescents with obesity, in the placebo-controlled, randomized controlled trial Combat-JUDO. The aim of this study was to evaluate effects of weekly injections of 2 mg exenatide extended release on secretory patterns of endogenous hormones during OGTT. Subjects and Measurements: This study was a pre-planned sub-study of the Combat-JUDO trial,